Biomedical statistics study on the correlation between peripheral blood follicular helper T cell subsets and primary Sjogren’s syndrome: T-cell subsets and primary Sjogren’s syndrome - Huang, Wei; Xu, Jinguo; Kong, Dehua; Ma, Min (Cellular and Molecular Biology, 2023)
To study the expressions of follicular helper T cell (Tfh) subsets——Tfh1, Tfh2, and Tfh17, in peripheral blood (PB) of primary Sjogren’s syndrome (PSS) patients in the active phase and remission period after treatment, and to analyze the pathogenic effects of Tfh subsets in PSS patients. The proportions of Tfh1, Tfh2, and Tfh17 were measured by flow cytometry in the healthy group, PSS patients group, active phase group, and remission phase group. Enzyme-linked immunosorbent assay was used to detect IL-21 expression in SS patients in active and remission stages. Biomedical statistics was used to analyze the correlation between Tfh subsets and SS disease activity index; and analyze the correlation between the proportions of Tfh subsets in the healthy group, primary group, active stage, and remission stage In contrast with the healthy group, the levels of Tfh1, Tfh2, and Tfh17 in CD4+ T cells of PSS patients were prominently reduced. PSS patients in the active phase had significantly lower Tfh1, Tfh2, and Tfh17 levels but remarkably higher IL-21 levels than in the remission phase. The contents of Tfh1, Tfh2, and Tfh17 are negatively correlated with the severity of PSS.